Role of exercise on insulin sensitivity and beta-cell function: is exercise sufficient for the prevention of youth-onset type 2 diabetes? - Joon Young Kim; Justin Y. Jeon (Korean Society of Pediatric Endocrinology, 2020)
Parallel with the current pediatric obesity epidemic, the escalating rates of youthonset type 2 diabetes mellitus (T2DM) have become a major public health burden. Although lifestyle modification can be the first-line prevention for T2DM in youths, there is a lack of evidence to establish optimal specific exercise strategies for obese youths at high risk for T2DM. The purpose of this narrative review is to summarize the potential impact of exercise on 2 key pathophysiological risk factors for T2DM, insulin sensitivity and β-cell function, among obese youths. The studies cited are grouped by use of metabolic tests, i.e., direct and indirect measures of insulin sensitivity and β-cell function. In general, there are an increasing number of studies that demonstrate positive effects of aerobic exercise, resistance exercise, and the 2 combined on insulin sensitivity. However, a lack of evidence exists for the effect of any exercise modality on β-cell functional improvement. We also suggest a future direction for research into exercise medical prevention of youth-onset T2DM. These suggestions focus on the effects of exercise modalities on emerging biomarkers of T2DM risk.